Ni-based metal-alkali-acid multifunctional catalyst as well as preparation method and application thereof
By using Ni-MO-Al hydrotalcite precursor oxide with a layered porous structure, the Ni-based metal-base-acid multifunctional catalyst was prepared, and the existing Ni-based catalysts had poor circulation stability in the semi-hydrogenation reaction of dimethyl maleate was solved, high selectivity and long-term stability were achieved, and production costs were reduced.
Patent Information
- Application Number
- CN202411904831.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
In the semi-hydrogenation reaction of dimethyl maleate, the existing Ni-based catalysts have problems such as poor circulation stability, easy aggregation or loss of active metals, complex preparation process and high cost.
Ni-MO-Al hydrotalcite precursor oxide with a layered porous structure was used as a support to prepare Ni-based metal-base-acid multifunctional catalyst by efficient in situ desolution method, and the synergistic catalysis of the multi-active center was used to achieve highly selective preparation of dimethyl succinate.
The long-term stability of the catalyst is achieved, the catalytic activity and selectivity are improved, the production cost is reduced, and the preparation process is simplified.
Smart Images

Figure CN119701970A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysis, and in particular relates to a Ni-based metal-base-acid multifunctional catalyst and a preparation method and application thereof. Background Art
[0002] Dimethyl succinate (DMS) is a colorless or light yellow liquid substance at room temperature. As an important chemical intermediate, it is widely used in food, fragrance, medicine, coating, rubber, plastic and other industries for the synthesis of light stabilizers, high-grade coatings, fungicides and pharmaceutical intermediates. At present, the synthesis process of dimethyl succinate is to use dimethyl maleate (DMM) and hydrogen as raw materials and to obtain it through partial hydrogenation reaction using precious metal or non-precious metal catalysts.
[0003] Catalysts for achieving rapid hydrogenation of unsaturated bonds under mild conditions mainly include precious metal catalysts, Cu-based catalysts, and Ni-based catalysts. Precious metal catalysts are mainly based on Pd or Pt. For example, the Chinese patent with publication number CN103464153A discloses a hydrogenation catalyst for producing dimethyl succinate and a preparation method thereof. The catalyst uses a resin-based spherical activated carbon with a microporous structure as a carrier, first loads Pd by a liquid phase precipitation method, and then loads WO3. It is prepared by washing, drying, and roasting. The catalyst preparation process is complex and the cost is relatively high. Cu-based catalysts have a wide range of raw material resources, low price, simple preparation method, and are easy to mass produce, with high economy. However, it is easy to hydrogenate the CO bond in the ester hydrogenation reaction to obtain deep hydrogenation products such as γ-butyrolactone and 1,4-butanediol. For example, Chinese patent publication number CN1850328A discloses a highly selective catalyst for preparing 1,4-butanediol and a preparation method thereof. The catalyst is a Cu / ZnO / carrier metal oxide ternary system. The method adopts a commonly used co-precipitation method to prepare the catalyst. Under stirring conditions, co-current dropwise precipitation is performed. Since the active metals are not precipitated at the same time, some of the active metals are easily wrapped, which is not conducive to the high dispersion of the metals, thereby affecting the activity and selectivity of the catalyst.
[0004] In comparison, Ni-based catalysts have a high activation ability for hydrogen due to the two electron vacancies in the d orbital of Ni atoms, and are more nucleophilic due to their small size as "first-row" transition metals. At the same time, nickel metal has the advantages of low cost and high activity. However, conventional supported Ni-based catalysts use carbon materials or simple metal oxides as carriers. Due to the weak interaction between the metal and the carrier, Ni particles are prone to aggregation or loss during high-temperature reduction and liquid-phase hydrogenation, and large-particle metal Ni sites are prone to carbon deposition and deactivation, resulting in poor catalyst cycle stability. Frequent catalyst replacement will affect production efficiency and increase production costs. Summary of the invention
[0005] In view of the technical problems existing in the semi-hydrogenation reaction of dimethyl maleate by the above Ni-based catalyst, the purpose of the present invention is to provide a Ni-based metal-base-acid multifunctional catalyst, preparation method and application thereof, which is cheap, simple to prepare, can catalyze the semi-hydrogenation of dimethyl maleate to succinate diester with high specificity and long-term stability. The present invention first synthesizes a Ni-MO-Al hydrotalcite precursor oxide (M is one of Mg, Ca, Sr, Ba, Cd and Zn) with a layered porous structure, and then prepares a Ni-based metal-base-acid multifunctional catalyst by an efficient in-situ precipitation method. The present invention makes full use of the synergistic catalysis of the multiple active centers of the catalyst, including the MO basic site, the Al2O3 acidic site and the Ni metal hydrogenation active site, and realizes the highly selective preparation of the target product dimethyl succinate under mild conditions through the metal-base-acid multi-site synergistic catalysis and the strong metal carrier interaction.
[0006] To achieve the above object, the technical solution of the present invention is as follows:
[0007] On one hand, the present invention provides a Ni-based metal-base-acid multifunctional catalyst, wherein the general formula of the Ni-based metal-base-acid multifunctional catalyst is Ni-MO-Al2O3, wherein MO represents an oxide selected from Mg, Ca, Sr, Ba, Cd and Zn; the catalyst uses Al2O3 as a carrier, Ni and MO as metal active components, the carrier Al2O3 maintains a partial lamellar skeleton structure of hydrotalcite at the nanoscale, and the metal active component nickel metal nanoparticles and MO are uniformly distributed inside or on the inner surface of the Al2O3 skeleton, that is, the Ni-MO nanoparticles are uniformly grown on the lamellar pore walls of the Al2O3 nanosheets.
[0008] Furthermore, in terms of mass percentage, the contents of the components in the Ni-MO-Al2O3 are as follows: Ni is 20-45%, MO is 10-35%, and Al2O3 is 35-60%.
[0009] Furthermore, the specific surface area of the Ni-MO-Al2O3 is 125 to 140 m 2 ·g -1 The average pore size is 9-20 nm and the pore volume is 0.35-0.70 cm 3 ·g -1 , Ni particle size is 4.5~6.5nm.
[0010] Another aspect of the present invention provides a method for preparing the Ni-based metal-base-acid multifunctional catalyst as described above, comprising the following steps:
[0011] (1) dissolving NaOH in deionized water to prepare a NaOH solution; dissolving Na2CO3 in deionized water to prepare a Na2CO3 solution; dissolving nickel salt, M salt and aluminum salt in deionized water to prepare a metal salt solution;
[0012] (2) dropping the metal salt solution and the NaOH solution into the Na2CO3 solution simultaneously for precipitation titration;
[0013] (3) aging the precipitation solution after the precipitation is completed to obtain a precursor precipitate;
[0014] (4) The precursor precipitate is washed, dried, and activated to obtain the catalyst Ni-MO-Al2O3.
[0015] Furthermore, in step (1), the nickel salt, M salt and aluminum salt are solutions of their nitrates, acetates or other soluble salts; the molar fraction ratio of the nickel salt, M salt and aluminum salt is 1 to 3:1 to 3:1, and the molar fraction ratio of the nickel salt + M salt and aluminum salt is 2 to 4:1.
[0016] Furthermore, in the step (1), the total concentration of the metal salt solution is 0.3-1.0 mol / L, and the volume is 75-250 mL; the concentration of the NaOH solution is 1-1.8 mol / L, and the volume is 150-200 mL; the concentration of the Na2CO3 solution is 0.3-0.6 mol / L, and the volume is 150-200 mL.
[0017] Furthermore, in the precipitation titration process in step (2), the volume flow ratio of the metal salt solution and the NaOH solution is controlled to be 0.75-2.5:1.5-2, the titration duration is 1-6 hours, the pH value of the mixed solution is maintained at 9-11, and the operating temperature is 50-100° C.; in step (3), the aging temperature is 20-30° C. and the time is 12-36 hours.
[0018] Furthermore, the washing liquid used in step (4) is deionized water, ethanol or a mixed solution of ethanol / water with a volume ratio of 3:1 to 1:3, and the number of washings is 3 to 5 times; the drying temperature is 70 to 200° C., and the drying time is 8 h to 20 h.
[0019] Furthermore, the activation treatment method in step (4) includes: activation treatment one: first calcining at 350°C to 600°C for 3h to 6h in a static air or flowing nitrogen atmosphere, with a heating rate of 2°C / min to 10°C / min; then reducing at 400°C to 600°C for 3h to 5h in a hydrogen or H2 / N2 mixed gas atmosphere with a hydrogen content of 10 to 100%, with a heating rate of 2°C / min to 10°C / min; or activation treatment two: directly reducing at 400°C to 600°C for 3h to 5h in a hydrogen or H2 / N2 mixed gas atmosphere with a hydrogen content of 10 to 100%, with a heating rate of 2°C / min to 10°C / min.
[0020] Another aspect of the present invention provides the use of the Ni-based metal-base-acid multifunctional catalyst as described above for preparing succinic acid diester by semi-hydrogenation of dimethyl maleate.
[0021] The Ni-based metal-base-acid multifunctional catalyst of the present invention adopts a 1L high-pressure intermittent hydrogenation reactor to evaluate the hydrogenation activity of dimethyl maleate: in this test, 30-150g dimethyl maleate, 0.6-3g of 20 to 60 mesh Ni-MO-Al2O3 catalyst and 270-700mL of anhydrous methanol solvent are added to the high-pressure reactor. After sealing, the reaction system is first washed with N2 and H2 for 5 times, and then pressurized to the desired pressure with pure hydrogen. Under the conditions of 100-250°C and 1-5MPa, the reaction is carried out for 20min-6h, and the stirring speed is 200-600r / min. The product after the reaction is analyzed by a gas chromatograph (Aglient7890A), and the content of each component is determined by a hydrogen ion flame detector (FID) on an HP-5 capillary column.
[0022] The hydrogenation process of dimethyl maleate is complex and belongs to a multi-step cascade reaction. In addition to dimethyl succinate (DMS), the product system also has byproducts such as γ-butyrolactone (GBL), 1,4-butanediol (BDO) and tetrahydrofuran (THF). The hydrogenation process involves the mixed hydrogenation of multiple functional groups such as C=C, C=O, -CO-OR, including polyester hydrogenation reaction, lactone hydrogenation reaction, intramolecular dehydration reaction, etc., and there is an inhibitory effect of chemical equilibrium. Especially under high temperature and pressure, -COO- and C=O are more easily activated, and the reaction rate of hydrogenation to produce other byproducts will be accelerated. Therefore, in order to achieve the complete conversion of dimethyl maleate and the high selectivity of dimethyl succinate, it is required that the catalyst used can not only activate C=C, but also inhibit the hydrogenation of C=O and the hydrogenolysis of -COO-. The Ni-based metal-base-acid multifunctional catalyst of the present invention is a supported metal catalyst prepared by a structural topological transformation process of a layered double hydroxide (LDHs) precursor. Reduction treatment of the LDHs precursor in a hydrogen atmosphere will result in highly dispersed metal nanoparticles loaded on a mixed metal oxide matrix, which has a topological transformation effect and a confinement effect, so that the metal in the catalyst presents a high degree of dispersion at the atomic level, and a dispersed, uniform and stable active site can be obtained. At the same time, the lattice confinement effect of this type of hydrotalcite catalyst can regulate the metal active site, and can also effectively inhibit the aggregation behavior of active metal atoms in the catalyst. The "surface trap structure" and "surface network structure" it has can provide anchoring points for active components, thereby improving the dispersion and stability of active components on the catalyst surface. Hydrotalcite-like has the characteristics of surface acid-base controllability, and the controllable acid-base site is conducive to the catalytic transfer hydrogenation of dimethyl maleate to dimethyl succinate.
[0023] Therefore, the design idea of the present invention is to provide a Ni-MO-Al2O3 ternary catalyst, which is composed of active components Ni, M (one of Mg, Ca, Sr, Ba, Cd and Zn) and Al2O3, and is easier to adjust the metal-support interaction (for example, electronic metal-support interaction, metal / support acid-base interaction) than the supported nickel-based catalyst prepared by the traditional method. The principle of multifunctional catalysis is shown in the attached Figure 1 :First, the surface Ni 0 The species act as active sites for C=C to CC hydrogen dissociation adsorption to active hydrogen atoms. In the second step, the Lewis acid sites (Al 3+ ) adsorbs and polarizes the oxygen atom on the ester group (O=CO) by p-π conjugation effect, and at the same time, the strong basic position (M 2+ -O 2- The Ni pair is easy to interact with the π* acceptor orbital on the ester group (O=CO) on the carbon atom, thereby promoting the adsorption occupation of the C=O / CO bond in the DMM molecule and inhibiting its further hydrogenation.0 This ternary synergistic catalytic effect between species and base sites and acid sites, as well as the strong metal carrier base-acid interaction, is conducive to the activation adsorption of DMM and the subsequent hydrogenation reaction, so that the catalyst shows excellent low-temperature activity, high high-temperature specificity and hydrogenation activity and selectivity in the dimethyl maleate reaction after reduction activation. Dimethyl maleate can be almost completely converted at a high feedstock space velocity, and a high selectivity for dimethyl succinate is obtained, with almost no by-products. For example, under the conditions of reaction temperature of 50-200°C and reaction pressure of 2-6MPa, the conversion rate of dimethyl maleate can reach 100%, and the selectivity of dimethyl succinate is 100%.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1) The Ni-based metal-base-acid multifunctional catalyst of the present invention has a long service life, a simple preparation process, a low cost, a strong metal-carrier interaction, a uniform distribution of the active phase, a high degree of dispersion, and the active metal sites are not easy to migrate or lose under high temperature or liquid phase conditions.
[0026] 2) The present invention prepares Ni-based metal-base-acid multifunctional catalyst by an efficient in-situ desolvation method. After reduction, the active metal Ni is dissolved from the skeleton structure to the catalyst surface. 0 The site rapidly hydrogenates the reaction from C=C to CC, and the Lewis acid sites (Al 3+ ) adsorbs and polarizes the oxygen atom on the ester group (O=CO), while the medium-strong alkaline position (M 2+ -O 2- The two together inhibit the adsorption between the ester group (O=C) and the active component, effectively reducing the loss of active components. The three metal base and acid sites work together to effectively improve the hydrogenation activity of the catalyst and extend the service life of the catalyst.
[0027] 3) The Ni-based metal-base-acid multifunctional catalyst of the present invention has high high temperature specificity in hydrogenation reactions. The addition of alkaline additives reduces the strong acid strength on the catalyst surface, enhances the interaction between the metal active components and the carrier, and increases the dispersion of the active metal; more importantly, the alkaline sites can effectively inhibit the formation of carbon deposit intermediates, avoid the accumulation of carbon on the catalyst surface covering the active sites, and improve the reaction activity and stability of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a working principle diagram of the Ni-based metal-base-acid multifunctional catalyst of the present invention;
[0029] Figure 2 is the X-ray diffraction spectrum of the catalyst precursor precipitation, calcined sample and H2 activated sample of Example 4;
[0030] Figure 3 The N2 adsorption-desorption curve (left) and pore size distribution (right) of the catalyst of Example 3. DETAILED DESCRIPTION
[0031] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0032] Example 1
[0033] 1) At room temperature, weigh an appropriate amount of NaOH and dissolve it in 200 mL of deionized water to prepare a NaOH solution (concentration is 1 mol / L); weigh an appropriate amount of Na2CO3 and dissolve it in 200 mL of deionized water to prepare a Na2CO3 solution (concentration is 0.3 mol / L); weigh 7.3 g of nickel nitrate hexahydrate, 7.4 g of zinc nitrate hexahydrate and 9.4 g of aluminum nitrate nonahydrate and dissolve them in 150 mL of deionized water (the total concentration of the metal salt solution is 0.5 mol / L, and the molar fraction ratio of the nickel salt, zinc salt and aluminum salt is 1:1:1), stir at a speed of 800 r / min, and stir evenly for 1 h to prepare a metal salt solution.
[0034] 2) Place the prepared Na2CO3 solution in a 1L beaker, raise the operating temperature to 50°C, then place the prepared metal salt solution and NaOH solution in burettes respectively, control the volume flow ratio of the metal salt solution and the NaOH solution to be 1.5:2, stir at a rate of 800r / min, and maintain the pH value of the mixed solution at 9, and titrate for 1.5h. After the crystallization is completed, the precipitation solution is cooled to 20°C and aged for 24h at a stirring rate of 550r / min to obtain a precursor precipitate.
[0035] 3) The precursor precipitate was repeatedly washed with deionized water for 6 times until neutral, placed in an oven at 100°C for 12 hours, moved to a tube furnace for activation treatment, calcined at 350°C for 6 hours in static air at a heating rate of 0.5°C / min, cooled to room temperature, and then reduced from room temperature to 550°C for 3 hours in a 10% H2 / N2 atmosphere, and then taken out after cooling to room temperature to obtain Catalyst 1. The active metal content and texture and structural parameters of Catalyst 1 are shown in Table 1.
[0036] 4) Catalyst evaluation conditions: In this test, 30 g of dimethyl maleate, 0.6 g of catalyst 1 screened at 30 mesh, and 270 mL of anhydrous methanol solvent were added to a 1L high-pressure intermittent hydrogenation reactor. After sealing, the reaction system was washed with N2 and H2 for 5 times, and then pressurized to 1 MPa with pure hydrogen. The reaction temperature and pressure were set at 100°C and 1 MPa, and the stirring speed was 600 r / min for continuous reaction. During the reaction, a small amount of reaction material was removed through the sampling port every 10 minutes and its composition was analyzed. The products after the reaction were analyzed by gas chromatograph (Aglient 7890A), and the content of each component was determined by hydrogen ion flame detector (FID) on HP-5 capillary column. The conversion rate of the reaction substrate and the selectivity of the product were calculated, and the evaluation results are shown in Table 2.
[0037] Example 2
[0038] 1) At room temperature, weigh an appropriate amount of NaOH and dissolve it in 150 mL of deionized water to prepare a NaOH solution (concentration is 1 mol / L); weigh an appropriate amount of Na2CO3 and dissolve it in 150 mL of deionized water to prepare a Na2CO3 solution (concentration is 0.3 mol / L); weigh 10.9 g of nickel nitrate hexahydrate, 5.6 g of zinc nitrate hexahydrate and 7.2 g of aluminum nitrate nonahydrate and dissolve them in 200 mL of deionized water (the total concentration of the metal salt solution is 0.375 mol / L, and the molar fraction ratio of the nickel salt, zinc salt and aluminum salt is 2:1:1), stir at a speed of 500 r / min, and stir evenly for 40 min to prepare a metal salt solution.
[0039] 2) Place the prepared Na2CO3 solution in a 1L beaker, raise the operating temperature to 75°C, then place the prepared metal salt solution and NaOH solution in burettes respectively, control the volume flow ratio of the metal salt solution and the NaOH solution to be 2:1.5, stir at a rate of 600r / min, and maintain the pH value of the mixed solution at 11, and titrate for 2.8h. After the crystallization is completed, the precipitation solution is cooled to 25°C and aged for 36h at a stirring rate of 500r / min to obtain a precursor precipitate.
[0040] 3) The precursor precipitate was repeatedly washed with deionized water for 5 times until neutral, placed in an oven at 90°C for 12 hours, moved to a tube furnace for activation treatment, calcined at 500°C for 4 hours in static air at a heating rate of 8°C / min, cooled to room temperature, and then reduced from room temperature to 600°C for 3 hours in a 20% H2 / N2 atmosphere, and then taken out after cooling to room temperature to obtain Catalyst 2. The active metal content and texture and structural parameters of Catalyst 2 are shown in Table 1.
[0041] 4) Catalyst evaluation conditions: In this test, 100g of dimethyl maleate, 2g of catalyst 2 screened at 20 mesh, and 700mL of anhydrous methanol solvent were added to a 1L high-pressure intermittent hydrogenation reactor. After sealing, the reaction system was washed with N2 and H2 for 5 times, and then pressurized to 2MPa with pure hydrogen. The reaction temperature and pressure were set at 100℃ and 2MPa, and the stirring speed was 500r / min for continuous reaction. During the reaction, a small amount of reaction material was removed through the sampling port every 10min and its composition was analyzed. The products after the reaction were analyzed by gas chromatograph (Aglient 7890A), and the content of each component was determined by hydrogen ion flame detector (FID) on HP-5 capillary column. The conversion rate of the reaction substrate and the selectivity of the product were calculated, and the evaluation results are shown in Table 2.
[0042] Example 3
[0043] 1) At room temperature, weigh an appropriate amount of NaOH and dissolve it in 200 mL of deionized water to prepare a NaOH solution (concentration is 1.8 mol / L); weigh an appropriate amount of Na2CO3 and dissolve it in 200 mL of deionized water to prepare a Na2CO3 solution (concentration is 0.6 mol / L); weigh 7.3 g of nickel nitrate hexahydrate, 6.4 g of zinc nitrate hexahydrate and 9.4 g of aluminum nitrate nonahydrate and dissolve them in 250 mL of deionized water (the total concentration of the metal salt solution is 0.3 mol / L, and the molar fraction ratio of the nickel salt, magnesium salt and aluminum salt is 1:1:1), stir at a speed of 600 r / min, and stir evenly for 30 min to prepare a metal salt solution.
[0044] 2) Place the prepared Na2CO3 solution in a 1L beaker, raise the operating temperature to 75°C, then place the prepared metal salt solution and NaOH solution in burettes respectively, control the volume flow ratio of the metal salt solution and the NaOH solution to 2.5:2, stir at a rate of 540r / min, and maintain the pH value of the mixed solution at 10, and titrate for 1.3h. After the crystallization is completed, the precipitation solution is cooled to 30°C and aged for 12h at a stirring rate of 660r / min to obtain a precursor precipitate.
[0045] 3) The precursor precipitate was repeatedly washed with deionized water for 4 times until neutral, placed in an oven at 70°C for 12 hours, moved to a tube furnace for activation treatment, calcined at 450°C for 5 hours in static air at a heating rate of 1°C / min, cooled to room temperature, and then reduced from room temperature to 550°C for 3 hours in a 50% H2 / N2 atmosphere, and then taken out after cooling to room temperature to obtain Catalyst 3. The active metal content and texture and structural parameters of Catalyst 3 are shown in Table 1.
[0046] 4) Catalyst evaluation conditions: In this test, 30 g of dimethyl maleate, 0.6 g of catalyst 3 screened at 30 mesh, and 270 mL of anhydrous methanol solvent were added to a 1L high-pressure intermittent hydrogenation reactor. After sealing, the reaction system was washed with N2 and H2 for 5 times, and then pressurized to 3 MPa with pure hydrogen. The reaction temperature and pressure were set at 150°C and 3 MPa, and the stirring speed was 600 r / min for continuous reaction. During the reaction, a small amount of reaction material was removed through the sampling port every 10 minutes and its composition was analyzed. The products after the reaction were analyzed by gas chromatograph (Aglient 7890A), and the content of each component was determined by hydrogen ion flame detector (FID) on HP-5 capillary column. The conversion rate of the reaction substrate and the selectivity of the product were calculated, and the evaluation results are shown in Table 2.
[0047] Example 4
[0048] 1) At room temperature, weigh an appropriate amount of NaOH and dissolve it in 150 mL of deionized water to prepare a NaOH solution (concentration is 1.3 mol / L); weigh an appropriate amount of Na2CO3 and dissolve it in 150 mL of deionized water to prepare a Na2CO3 solution (concentration is 0.5 mol / L); weigh 11.0 g of nickel nitrate hexahydrate, 4.8 g of magnesium nitrate hexahydrate and 7.2 g of aluminum nitrate nonahydrate and dissolve them in 190 mL of deionized water (the total concentration of the metal salt solution is 0.4 mol / L, and the molar fraction ratio of the nickel salt, magnesium salt and aluminum salt is 2:1:1), stir at a speed of 500 r / min, and stir evenly for 2 h to prepare a metal salt solution.
[0049] 2) Place the prepared Na2CO3 solution in a 1L beaker, raise the operating temperature to 95°C, then place the prepared metal salt solution and NaOH solution in burettes respectively, control the volume flow ratio of the metal salt solution and the NaOH solution to be 1.9:1.5, stir at a rate of 600r / min, and maintain the pH value of the mixed solution at 11, and titrate for 3.8h. After the crystallization is completed, the precipitation solution is cooled to 20°C and aged for 24h at a stirring rate of 660r / min to obtain a precursor precipitate.
[0050] 3) The precursor precipitate was repeatedly washed with deionized water for 4 times until neutral, placed in an oven at 90°C for 12 hours, moved to a tube furnace for activation treatment, calcined at 500°C for 4 hours in static air at a heating rate of 8°C / min, cooled to room temperature, and then reduced from room temperature to 600°C for 3 hours in a pure H2 atmosphere, and then taken out after cooling to room temperature to obtain catalyst 4. The active metal content and texture and structural parameters of catalyst 4 are shown in Table 1.
[0051] 4) Catalyst evaluation conditions: In this test, 100g of dimethyl maleate, 2g of catalyst 4 screened at 20 mesh, and 700mL of anhydrous methanol solvent were added to a 1L high-pressure intermittent hydrogenation reactor. After sealing, the reaction system was washed with N2 and H2 for 5 times, and then pressurized to 3MPa with pure hydrogen. The reaction temperature and pressure were set at 150℃ and 3MPa, and the stirring speed was 500r / min for continuous reaction. During the reaction, a small amount of reaction material was removed through the sampling port every 10min and its components were analyzed. The products after the reaction were analyzed by gas chromatograph (Aglient 7890A), and the content of each component was determined by hydrogen ion flame detector (FID) on HP-5 capillary column. The conversion rate of the reaction substrate and the selectivity of the product were calculated, and the evaluation results are shown in Table 2.
[0052] Example 5
[0053] 1) At room temperature, weigh an appropriate amount of NaOH and dissolve it in 200 mL of deionized water to prepare a NaOH solution (concentration is 1.5 mol / L); weigh an appropriate amount of Na2CO3 and dissolve it in 200 mL of deionized water to prepare a Na2CO3 solution (concentration is 0.45 mol / L); weigh 7.3 g of nickel nitrate hexahydrate, 5.9 g of calcium nitrate tetrahydrate and 9.4 g of aluminum nitrate nonahydrate and dissolve them in 100 mL of deionized water (the total concentration of the metal salt solution is 0.75 mol / L, and the molar fraction ratio of the nickel salt, calcium salt and aluminum salt is 1:1:1), stir at a speed of 600 r / min, and stir evenly for 4 h to prepare a metal salt solution.
[0054] 2) Place the prepared Na2CO3 solution in a 1L beaker, raise the operating temperature to 65°C, then place the prepared metal salt solution and NaOH solution in burettes respectively, control the volume flow ratio of the metal salt solution and the NaOH solution to be 1:2, stir at a rate of 540r / min, and maintain the pH value of the mixed solution at 10, and titrate for 4.4h. After the crystallization is completed, the precipitation solution is cooled to 25°C and aged for 12h at a stirring rate of 800r / min to obtain a precursor precipitate.
[0055] 3) The precursor precipitate was repeatedly washed with deionized water for 6 times until neutral, placed in an oven at 100°C for 12 hours, moved to a tube furnace for activation treatment, calcined at 450°C for 4 hours in static air at a heating rate of 2°C / min, cooled to room temperature, and then reduced from room temperature to 550°C for 3 hours in an 80% H2 / N2 atmosphere, and then taken out after cooling to room temperature to obtain Catalyst 5. The active metal content and texture and structural parameters of Catalyst 5 are shown in Table 1.
[0056] 4) Catalyst evaluation conditions: In this test, 30 g of dimethyl maleate, 0.6 g of catalyst 5 screened at 30 mesh, and 270 mL of anhydrous methanol solvent were added to a 1L high-pressure intermittent hydrogenation reactor. After sealing, the reaction system was washed with N2 and H2 for 5 times, and then pressurized to 3 MPa with pure hydrogen. The reaction temperature and pressure were set at 150°C and 3 MPa, and the stirring speed was 600 r / min for continuous reaction. During the reaction, a small amount of reaction material was removed through the sampling port every 10 minutes and its composition was analyzed. The products after the reaction were analyzed by gas chromatograph (Aglient 7890A), and the content of each component was determined by hydrogen ion flame detector (FID) on HP-5 capillary column. The conversion rate of the reaction substrate and the selectivity of the product were calculated, and the evaluation results are shown in Table 2.
[0057] Example 6
[0058] 1) At room temperature, weigh an appropriate amount of NaOH and dissolve it in 170 mL of deionized water to prepare a NaOH solution (concentration is 1.5 mol / L); weigh an appropriate amount of Na2CO3 and dissolve it in 170 mL of deionized water to prepare a Na2CO3 solution (concentration is 0.45 mol / L); weigh 9.4 g of nickel nitrate hexahydrate, 5.1 g of calcium nitrate tetrahydrate and 8.2 g of aluminum nitrate nonahydrate and dissolve them in 115 mL of deionized water (the total concentration of the metal salt solution is 0.65 mol / L, and the molar fraction ratio of the nickel salt, magnesium salt and aluminum salt is 1.5:1:1), stir at a speed of 550 r / min, and stir evenly for 3 h to prepare a metal salt solution.
[0059] 2) Place the prepared Na2CO3 solution in a 1L beaker, raise the operating temperature to 65°C, then place the prepared metal salt solution and NaOH solution in burettes respectively, control the volume flow ratio of the metal salt solution and the NaOH solution to be 1.15:1.7, stir at a rate of 560r / min, and maintain the pH value of the mixed solution at 10, and titrate for 1.6h. After the crystallization is completed, the precipitation solution is cooled to 30°C and aged for 36h at a stirring rate of 660r / min to obtain a precursor precipitate.
[0060] 3) The precursor precipitate was repeatedly washed with deionized water for 4 times until neutral, placed in an oven at 95°C for 12 hours, moved to a tube furnace for activation treatment, calcined at 480°C for 4 hours in static air at a heating rate of 5°C / min, cooled to room temperature, and then reduced from room temperature to 400°C for 5 hours in a 10% H2 / N2 atmosphere, and then taken out after cooling to room temperature to obtain Catalyst 6. The active metal content and texture and structural parameters of Catalyst 6 are shown in Table 1.
[0061] 4) Catalyst evaluation conditions: In this test, 50g of dimethyl maleate, 1g of catalyst 6 screened at 30 mesh, and 450mL of anhydrous methanol solvent were added to a 1L high-pressure intermittent hydrogenation reactor. After sealing, the reaction system was washed with N2 and H2 for 5 times, and then pressurized to 4MPa with pure hydrogen. The reaction temperature and pressure were set at 200℃ and 4MPa, and the stirring speed was 600r / min for continuous reaction. During the reaction, a small amount of reaction material was removed through the sampling port every 10min and its composition was analyzed. The reaction products were analyzed by gas chromatograph (Aglient 7890A), and the content of each component was determined by hydrogen ion flame detector (FID) on HP-5 capillary column. The conversion rate of the reaction substrate and the selectivity of the product were calculated, and the evaluation results are shown in Table 2.
[0062] Example 7
[0063] 1) At room temperature, weigh an appropriate amount of NaOH and dissolve it in 150 mL of deionized water to prepare a NaOH solution (concentration is 1.5 mol / L); weigh an appropriate amount of Na2CO3 and dissolve it in 150 mL of deionized water to prepare a Na2CO3 solution (concentration is 0.45 mol / L); weigh 11.3 g of nickel nitrate hexahydrate, 5.8 g of cadmium nitrate tetrahydrate and 7.2 g of aluminum nitrate nonahydrate and dissolve them in 125 mL of deionized water (the total concentration of the metal salt solution is 0.6 mol / L, and the molar fraction ratio of the nickel salt, magnesium salt and aluminum salt is 2:1:1), stir at a speed of 500 r / min, and stir evenly for 2.5 h to prepare a metal salt solution.
[0064] 2) Place the prepared Na2CO3 solution in a 1L beaker, raise the operating temperature to 65°C, then place the prepared metal salt solution and NaOH solution in burettes respectively, control the volume flow ratio of the metal salt solution and the NaOH solution to be 1.25:1.5, stir at a rate of 600r / min, and maintain the pH value of the mixed solution at 11, and titrate for 5.7h. After the crystallization is completed, the precipitation solution is cooled to 25°C and aged for 24h at a stirring rate of 660r / min to obtain a precursor precipitate.
[0065] 3) The precursor precipitate was repeatedly washed with deionized water for 5 times until it was neutral, dried in an oven at 90°C for 12 hours, moved to a tube furnace for activation treatment, and reduced at 600°C from room temperature for 4 hours in a 50% H2 / N2 atmosphere, and then taken out after cooling to room temperature to obtain Catalyst 7. The active metal content and texture and structural parameters of Catalyst 7 are shown in Table 1.
[0066] 4) Catalyst evaluation conditions: In this test, 100g of dimethyl maleate, 2g of catalyst 7 screened at 60 mesh, and 700mL of anhydrous methanol solvent were added to a 1L high-pressure intermittent hydrogenation reactor. After sealing, the reaction system was washed with N2 and H2 for 5 times, and then pressurized to 4MPa with pure hydrogen. The reaction temperature and pressure were set at 200℃ and 4MPa, and the stirring speed was 500r / min for continuous reaction. During the reaction, a small amount of reaction material was removed through the sampling port every 10min and its composition was analyzed. The products after the reaction were analyzed by gas chromatograph (Aglient 7890A), and the content of each component was determined by hydrogen ion flame detector (FID) on HP-5 capillary column. The conversion rate of the reaction substrate and the selectivity of the product were calculated, and the evaluation results are shown in Table 2.
[0067] Example 8
[0068] 1) At room temperature, weigh an appropriate amount of NaOH and dissolve it in 200 mL of deionized water to prepare a NaOH solution (concentration is 1.3 mol / L); weigh an appropriate amount of Na2CO3 and dissolve it in 200 mL of deionized water to prepare a Na2CO3 solution (concentration is 0.5 mol / L); weigh 13.1 g of nickel nitrate hexahydrate, 3.9 g of barium nitrate and 5.6 g of aluminum nitrate nonahydrate and dissolve them in 75 mL of deionized water (the total concentration of the metal salt solution is 1 mol / L, and the molar fraction ratio of the nickel salt, barium salt and aluminum salt is 3:1:1), stir at a speed of 500 r / min, and stir evenly for 6 h to prepare a metal salt solution.
[0069] 2) Place the prepared Na2CO3 solution in a 1L beaker, raise the operating temperature to 65°C, then place the prepared metal salt solution and NaOH solution in burettes respectively, control the volume flow ratio of the metal salt solution and the NaOH solution to 0.75:2, stir at a rate of 500r / min, and maintain the pH value of the mixed solution at 9, and titrate for 6h. After the crystallization is completed, the precipitation solution is cooled to 30°C and aged for 36h at a stirring rate of 660r / min to obtain a precursor precipitate.
[0070] 3) The precursor precipitate was repeatedly washed with deionized water for 4 times until it was neutral, dried in an oven at 200°C for 12 hours, moved to a tube furnace for activation treatment, and then reduced from room temperature to 400°C for 5 hours in a pure H2 atmosphere, and then taken out after cooling to room temperature to obtain Catalyst 8. The active metal content and texture and structural parameters of Catalyst 8 are shown in Table 1.
[0071] 4) Catalyst evaluation conditions: In this test, 30 g of dimethyl maleate, 0.6 g of catalyst 8 screened at 30 mesh, and 270 mL of anhydrous methanol solvent were added to a 1L high-pressure intermittent hydrogenation reactor. After sealing, the reaction system was washed with N2 and H2 for 5 times, and then pressurized to 5 MPa with pure hydrogen. The reaction temperature and pressure were set at 250°C and 5 MPa, and the stirring speed was 600 r / min for continuous reaction. During the reaction, a small amount of reaction material was removed through the sampling port every 10 minutes and its composition was analyzed. The products after the reaction were analyzed by gas chromatograph (Aglient 7890A), and the content of each component was determined by hydrogen ion flame detector (FID) on HP-5 capillary column. The conversion rate of the reaction substrate and the selectivity of the product were calculated, and the evaluation results are shown in Table 2.
[0072] Example 9
[0073] 1) At room temperature, weigh an appropriate amount of NaOH and dissolve it in 170 mL of deionized water to prepare a NaOH solution (concentration is 1 mol / L); weigh an appropriate amount of Na2CO3 and dissolve it in 170 mL of deionized water to prepare a Na2CO3 solution (concentration is 0.3 mol / L); weigh 7.3 g of nickel nitrate hexahydrate, 5.3 g of strontium nitrate and 9.4 g of aluminum nitrate nonahydrate and dissolve them in 190 mL of deionized water (the total concentration of the metal salt solution is 0.4 mol / L, and the molar fraction ratio of the nickel salt, strontium salt and aluminum salt is 1:1:1), stir at a speed of 550 r / min, and stir evenly for 50 min to prepare a metal salt solution.
[0074] 2) Place the prepared Na2CO3 solution in a 1L beaker, raise the operating temperature to 60°C, then place the prepared metal salt solution and NaOH solution in burettes respectively, control the volume flow ratio of the metal salt solution and the NaOH solution to be 1.9:1.7, stir at a rate of 560r / min, and maintain the pH value of the mixed solution at 10, and titrate for 1.6h. After the crystallization is completed, the precipitation solution is cooled to 25°C and aged for 12h at a stirring rate of 660r / min to obtain a precursor precipitate.
[0075] 3) The precursor precipitate was repeatedly washed with deionized water for 4 times until it was neutral, dried in an oven at 95°C for 12 hours, moved to a tube furnace for activation treatment, and then reduced from room temperature to 400°C for 5 hours in a 60% H2 / N2 atmosphere, and then taken out after cooling to room temperature to obtain Catalyst 9. The active metal content and texture and structural parameters of Catalyst 9 are shown in Table 1.
[0076] 4) Catalyst evaluation conditions: In this test, 50g of dimethyl maleate, 1g of catalyst 9 screened at 30 mesh, and 270mL of anhydrous methanol solvent were added to a 1L high-pressure intermittent hydrogenation reactor. After sealing, the reaction system was washed with N2 and H2 for 5 times, and then pressurized with pure hydrogen at 5MPa. The reaction temperature and pressure were set at 250℃ and 5MPa, and the stirring speed was 600r / min for continuous reaction. During the reaction, a small amount of reaction material was removed through the sampling port every 10min and its composition was analyzed. The reaction products were analyzed by gas chromatograph (Aglient 7890A), and the content of each component was determined by hydrogen ion flame detector (FID) on HP-5 capillary column. The conversion rate of the reaction substrate and the selectivity of the product were calculated, and the evaluation results are shown in Table 2.
[0077] Table 1 Active metal content and texture and structural parameters of Ni-based metal-base-acid multifunctional catalysts prepared in Examples 1 to 9
[0078]
[0079]
[0080] Table 2 Activity evaluation results of Ni-based metal-base-acid multifunctional catalysts prepared in Examples 1 to 9
[0081] Operation time / min DMM conversion rate / % DMS selectivity / % Catalyst 1 60 100 100 Catalyst 2 30 100 100 Catalyst 3 60 100 100 Catalyst 4 20 100 100 Catalyst 5 100 100 100 Catalyst 6 80 100 100 Catalyst 7 40 100 100 Catalyst 8 30 100 100 Catalyst 9 100 100 100
[0082] Characterization Test
[0083] (1) XRD characterization
[0084] Figure 2 The following are X-ray diffraction spectra of the catalyst precursor precipitation, calcined sample and H2 activated sample of Example 4. As shown in the figure, Example 4 has sharp and strong characteristic diffraction peaks of hydrotalcite at 2θ=11.2°(003), 23.1°(006), 34.9°(009), 39.1°(015), 47.0°(018), 60.8°(110) and 62.1°(113), which indicates that the hydrotalcite layered material has been successfully prepared. After calcination, the characteristic diffraction peak of LDH disappears due to the collapse of the layered structure, and it exists in the form of MgO-NiO periclase. After H2 activation, the diffraction peak of hydrotalcite disappears, and characteristic diffraction peaks appear at 44.3° and 51.9°, which correspond to the (111) and (200) crystal planes of Ni.
[0085] (2) BET characterization
[0086] Figure 3The N2 adsorption-desorption curve (left) and pore size distribution (right) of the catalyst of Example 3. As can be seen from the figure, Example 3 presents a typical IV type isotherm with obvious hysteresis loops, indicating that a good mesoporous structure is formed during the calcination process; from the pore size distribution diagram, it can be seen that the pore size distribution is around 14 nm.
[0087] The above description is only for better explaining the embodiments of the present invention, and is not intended to limit the present invention. Any modification or equivalent substitution that does not depart from the spirit and scope of the present invention shall fall within the scope of the present invention.
Claims
1. A Ni-based metal-base-acid multifunctional catalyst, characterized in that: The general formula of the Ni-based metal-base-acid multifunctional catalyst is Ni-MO-Al2O3, wherein MO represents an oxide selected from Mg, Ca, Sr, Ba, Cd and Zn; Al2O3 is used as a carrier, Ni and MO are metal active components, the carrier Al2O3 maintains a partial lamellar skeleton structure of hydrotalcite at the nanoscale, and the metal active component nickel metal nanoparticles and MO are uniformly distributed inside or on the inner surface of the Al2O3 skeleton, that is, the Ni-MO nanoparticles are uniformly grown on the lamellar pore walls of the Al2O3 nanosheets.
2. The Ni-based metal-base-acid multifunctional catalyst according to claim 1, characterized in that In terms of mass percentage, the contents of the components in the Ni-MO-Al2O3 are as follows: Ni is 20-45%, MO is 10-35%, and Al2O3 is 35-60%.
3. The Ni-based metal-base-acid multifunctional catalyst according to claim 2, characterized in that The specific surface area of Ni-MO-Al2O3 is 125-140m 2 ·g -1 The average pore size is 9-20 nm and the pore volume is 0.35-0.70 cm 3 ·g -1 , Ni particle size is 4.5~6.5nm.
4. The method for preparing the Ni-based metal-base-acid multifunctional catalyst according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) dissolving NaOH in deionized water to prepare a NaOH solution; dissolving Na2CO3 in deionized water to prepare a Na2CO3 solution; dissolving nickel salt, M salt and aluminum salt in deionized water to prepare a metal salt solution; (2) dropping the metal salt solution and the NaOH solution into the Na2CO3 solution simultaneously for precipitation titration; (3) aging the precipitation solution after the precipitation is completed to obtain a precursor precipitate; (4) The precursor precipitate is washed, dried, and activated to obtain the catalyst Ni-MO-Al2O3.
5. The method for preparing the Ni-based metal-base-acid multifunctional catalyst according to claim 4, characterized in that: In the step (1), the nickel salt, M salt and aluminum salt are solutions of their nitrates, acetates or other soluble salts; the molar fraction ratio of the nickel salt, M salt and aluminum salt is 1 to 3:1 to 3:1, and the molar fraction ratio of the nickel salt + M salt and aluminum salt is 2 to 4:
1.
6. The method for preparing the Ni-based metal-base-acid multifunctional catalyst according to claim 4, characterized in that: In the step (1), the total concentration of the metal salt solution is 0.3-1.0 mol / L, and the volume is 75-250 mL; the concentration of the NaOH solution is 1-1.8 mol / L, and the volume is 150-200 mL; the concentration of the Na2CO3 solution is 0.3-0.6 mol / L, and the volume is 150-200 mL.
7. The method for preparing the Ni-based metal-base-acid multifunctional catalyst according to claim 4, characterized in that: During the precipitation titration process in step (2), the volume flow ratio of the metal salt solution and the NaOH solution is controlled to be 0.75-2.5:1.5-2, the titration duration is 1-6 hours, the pH value of the mixed solution is maintained at 9-11, and the operating temperature is 50-100° C.; in step (3), the aging temperature is 20-30° C. and the aging time is 12-36 hours.
8. The method for preparing the Ni-based metal-base-acid multifunctional catalyst according to claim 4, characterized in that: The washing liquid used in step (4) is deionized water, ethanol or a mixed solution of ethanol / water with a volume ratio of 3:1 to 1:3, and the number of washings is 3 to 5 times; the drying temperature is 70 to 200° C., and the drying time is 8 hours to 20 hours.
9. The method for preparing the Ni-based metal-base-acid multifunctional catalyst according to claim 4, characterized in that: The activation treatment method in the step (4) includes: activation treatment one: first calcining at 350°C to 600°C for 3h to 6h in a static air or flowing nitrogen atmosphere, with a heating rate of 2°C / min to 10°C / min; then reducing at 400°C to 600°C for 3h to 5h in a hydrogen or H2 / N2 mixed gas atmosphere with a hydrogen content of 10 to 100%, with a heating rate of 2°C / min to 10°C / min; or activation treatment two: directly reducing at 400°C to 600°C for 3h to 5h in a hydrogen or H2 / N2 mixed gas atmosphere with a hydrogen content of 10 to 100%, with a heating rate of 2°C / min to 10°C / min.
10. Use of the Ni-based metal-base-acid multifunctional catalyst according to any one of claims 1 to 3, characterized in that: Used for semi-hydrogenation of dimethyl maleate to produce succinic acid diester.
Citation Information
Patent Citations
Method for preparing hydrogenation catalyst for producing dimethyl succinate
CN103464153A
High-selectivity catalyst for preparing 1,4-butanediol and its preparing method
CN1850328A
Cited By
Metal-acid-base site synergistic catalyst, preparation method and method for catalyzing multi-step cascade reaction thereof
CN122745886A